Control of Heating and Cooling of Adsorbers for Adsorption Cooling from Vehicle Exhaust Waste Heat using Programmable Logic Controller - Ephrem Ryan, Alphonsus (Universiti Malaysia Sarawak (UNIMAS), 2018)
In this research work, a new adsorber prototype using programmable logic controller (PLC) for adsorption cooling using exhaust waste heat was designed, built and successfully tested. PLC control application was applied to control the heating and cooling of these adsorbers. The timing for opening and closing of all the valves was accurate when comparing the digital timer in the program with stop watch and video recordings. In the normal control test, heating and cooling of adsorbers were heated and cooled in a straight forward sequence. Adsorber 1 was heated first, then the second and finally the third. Temperatures taken at specific points at the adsorbers were recorded. Based on the result collected, the highest and lowest temperature collected was 98 oC and 49 oC respectively from Adsorber 2. In the subsequent test, the pre- heat control, in which both adsorbers were heated up at the 8 th, 18th, 28th and all other corresponding intervals of 10 minutes until the 118th minutes. Based on the result collected, the highest and lowest temperature recorded was 103 oC and 45 oC respectively, also from Adsorber 2. This result shows that there is a future in using vehicle waste heat for heating the adsorbers for adsorption cooling system.